Development of Heyzine Based History E-Module on Material on the Spread of Islam in Banten and Evidence of It’s Heritage in Class X SMAN 1 Petir - Ningrum, Nadia Fitria; Nurhasanah, Ana; Fauzan, Rikza (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This research aims to determine the feasibility of a heyzine-based history e-module on the spread of Islam in Banten and evidence of its legacy at SMAN 1 Petir. The subjects of this research were class X C students with a total of 42 students. The method used is Research and Development (R&D) with the ADDIE model approach, which consists of 5 stages including: analysis, design, development, implementation, and evaluation. The feasibility of the history e-module is known from the validation results of material experts, media experts, student responses in small group limited trials and large group limited trials. The research results show that the feasibility level of the history e-module in terms of material for material experts is 94.5%, this percentage is included in the "very feasible" criteria so that the e-module can be used. Meanwhile, the feasibility of the history e-module in terms of media for media experts is 99%, this percentage is included in the "very feasible" criteria so that the e-module can be used. Trials limited to small groups of students obtained results of 86.5%, this percentage is included in the "very feasible" criteria so that the e-module can be used. Then, in a limited trial on large groups of students, the results were 83.3%, this percentage was included in the "very feasible" criteria so that the e-module could be used.